Psychological dynamics and organisational learning : From the dysfunctional organisation to the healthy organisation - James, Kim; Jarrett, Michael; Lucas, Donna (Cranfield University, 1996)
This paper explores the notion of organisation health as a factor contributing to the organisation’s ability to learn and create its future. Ill health or dysfunctionality is seen as blocking learning and change. The authors develop a diagnostic map, drawn from a psychodynamic perspective. This map aims to help change consultants pin-point the blocks to a healthy organisational culture in order to be more specific in their interventions to the client system.